ANALISIS PERANAN PERKEBUNAN KOPI DAN INDUSTRI PENGOLAHAN KOPI BUBUK DALAM MENGGERAKKAN PEREKONOMIAN WILAYAH DI KABUPATEN MERANGIN - Roja Magdalena, Feibe; Mara, Armen; Yanita, Mirawati (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2021)
The research purposed to analyze: (1)To describe the development of coffee plantation production in Merangin Regency, (2) To describe the development of the production of the ground coffee processing industry in Merangin Regency, (3) To analyze the role of coffee plantations in driving the regional economy in Merangin Regency in terms of labor aspects , (4) To analyze the role of the ground coffee processing industry in driving the regional economy in Merangin Regency in terms of labor aspects, (5) To analyze the relationship between coffee plantation production and the development of the ground coffee processing industry in Merangin Regency. The data used are secondary data. The data analysis method used is descriptive analysis, contribution analysis, location quotient analysis, multiplier effect analysis, shift share analysis and Pearson correlation analysis. This research was conducted in Merangin Regency as the research area and Jambi Province as the reference area. From the research results, it can be seen that the development of coffee plantation production and the ground coffee processing industry in Merangin Regency shows positive developments every year. Coffee plantations account for 5.85 percent and 0.020 percent of the ground coffee processing industry. Coffee plantation is a basic sector while the ground coffee processing industry is a non-base sector in Merangin Regency. With a ME value of 17.52 for coffee plantations and 6.44 for the ground coffee processing industry. From the results of the shift share analysis of coffee plantations, it is found that RPr is positive and RPs are negative. Meanwhile, the results of the shift share analysis of the ground coffee processing industry showed that RPr and RPs were positive. There is a positive relationship between coffee plantation production and the development of the ground coffee processing industry.